Fuzzy logic control of seat vibrations of a non-linear full vehicle model - Guclu, R (SPRINGER, 2005)
In this paper, the dynamic behavior of a non-linear eight degrees of freedom vehicle model having active suspensions and a fuzzy logic (FL) controlled passenger seat is examined. The non-linearity occurs due to dry friction on the dampers. Three cases of control strategies are taken into account. In the first case, only the passenger seat is controlled. In the second case, only the vehicle body is controlled. In the third case, both the vehicle body and the passenger seat are fully controlled at the same time. The time responses of the non-linear vehicle model due to road disturbance and the frequency responses are obtained for each control strategy. At the end, the performances of these strategies are compared.
Keywords: active suspensions; FL control; non-linear systems; vehicle vibrations; CONTROL LAWS; PERFORMANCE; SYSTEM; Engineering; Mechanics